Child Custody in Divorce: A Review of Islamic Law Against Modern Court Practice - Muhammad Arsyad; M. Anshari; Mawarni Fatma (PT. Anagata Sembagi Education, 2024)
This study also aims to evaluate the extent to which Islamic law can be applied or accommodated in the modern justice system in Indonesia. The method used is a normative legal approach, with a literature review of legal sources, such as Islamic legal texts, court decisions, and Indonesian laws and regulations relating to child custody. The main data were obtained from books, journals, scientific articles, and relevant court decisions. Data analysis was carried out by examining the application of Islamic legal principles related to child custody in modern court practices in Indonesia. This study also uses comparative analysis to compare Islamic legal principles with Indonesian positive law. The results of the study show that although Islamic law provides clear principles regarding child custody, modern court practices are often not fully in accordance with these principles. The courts prioritize positive law, although the welfare of the child remains the main consideration. Therefore, harmonization between Islamic law and positive law is needed so that court decisions are fairer and in accordance with the values ​​of Muslim society. This study emphasizes the importance of integrating Islamic legal principles into the Indonesian justice system to ensure decisions that are in the best interests of the child.